2018
DOI: 10.1074/jbc.m117.812784
|View full text |Cite
|
Sign up to set email alerts
|

Effects of allelic variations in the human myxovirus resistance protein A on its antiviral activity

Abstract: Only a minority of patients infected with seasonal influenza A viruses exhibits a severe or fatal outcome of infection, but the reasons for this inter-individual variability in influenza susceptibility are unclear. To gain further insights into the molecular mechanisms underlying this variability, we investigated naturally occurring allelic variations of the myxovirus resistance 1 (MX1) gene coding for the influenza restriction factor MxA. The interferon-induced dynamin-like GTPase consists of an N-terminal GT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 45 publications
(86 reference statements)
1
35
0
Order By: Relevance
“…It encodes a large GTPase, MxA, which mediates broad resistance to influenza and other viruses both in cell culture (Aebi et al 1989;Haller et al 2015) and transgenic mice (Deeg et al 2017;Hefti et al 1999;Pavlovic et al 1995). Interestingly, there are humans harboring allelic variants in MX1 (Duc et al 2012;Graf et al 2018;Tazi-Ahnini et al 2000) in heterozygous or homozygous form, but none of these variants have so far been linked to enhanced influenza virus susceptibility (Ciancanelli et al 2016;Graf et al 2018). Nevertheless, as outlined in this review, MX1 remains a strong candidate gene for controlling influenza virus susceptibility in humans.…”
Section: Introductionmentioning
confidence: 97%
“…It encodes a large GTPase, MxA, which mediates broad resistance to influenza and other viruses both in cell culture (Aebi et al 1989;Haller et al 2015) and transgenic mice (Deeg et al 2017;Hefti et al 1999;Pavlovic et al 1995). Interestingly, there are humans harboring allelic variants in MX1 (Duc et al 2012;Graf et al 2018;Tazi-Ahnini et al 2000) in heterozygous or homozygous form, but none of these variants have so far been linked to enhanced influenza virus susceptibility (Ciancanelli et al 2016;Graf et al 2018). Nevertheless, as outlined in this review, MX1 remains a strong candidate gene for controlling influenza virus susceptibility in humans.…”
Section: Introductionmentioning
confidence: 97%
“…It was found that nonsynonymous variations in the GTPase domain cause a loss of both antiviral and enzymatic activities (49 ). Additionally, it was demonstrated that these amino acid substitutions disrupt the interface for the GTPase domain dimerization required for the stimulation of the GTP hydrolysis (49 ). The results obtained convincingly show that the naturally occurring mutations in the human mx1 gene can influence MxA function, which may also explain the individual variations in influenza virus susceptibility in the human population.…”
Section: Reviewmentioning
confidence: 90%
“…Recently, naturally occurring allelic variations of mx1 coding for the influenza restriction factor MxA were investigated (49 ). It was found that nonsynonymous variations in the GTPase domain cause a loss of both antiviral and enzymatic activities (49 ).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations